Lupus enteritis as a flare up of systemic lupus erythematosus- a case report and review - Janga, Niketha; M., Jagadeesan; M., Kavitha M.; R., Kannan (International Journal of Advances in Medicine, 2021)
Systemic lupus erythematosus (SLE) generally affects young to middle-aged women, commonly presenting as a triad of fever, rash, and joint pain. Abdominal pain is a common symptom in patients with SLE. The leading causes of abdominal pain in SLE are lupus enteritis, pancreatitis, pseudo-obstruction, acalculous cholecystitis, mesenteric thrombosis, hepatic thrombosis, medications like (NSAIDS, MMF, steroids, HCQ), colon perforation. The incidence of abdominal pain in patients with SLE ranges from 8-40%, and the commonest cause is lupus enteritis. The following case describes a young woman presenting with lupus enteritis as a manifestation of SLE, the importance of early disease recognition, utilities of abdominal computed tomography (CT) in diagnosis, and current treatment protocols for lupus enteritis.